Vers un sentiment de réussite et de bien-être des élèves au sein du dispositif Devoirs faits : regards croisés d’élèves et d’adultes - Véronique Barthélemy (Éducation et Socialisation)
Since 2017, the Homework Done in Colleges program has been in place to help every student succeed. But what success are we talking about? In this article, we refer to educational success, referring to academic criteria as well as to well-being, self-confidence, sociability or personal development. To measure this success, we are building on area 2 (work organisation and cooperation) of the common curriculum of knowledge, skills and culture. We seek to identify how Homework Done promotes student educational success. In this review, the results of research and reports highlight the impact of this device on student behaviour, leading to progress and a sense of well-being. This is made possible by working conditions, by interactions between pupils or between pupils and teachers and by the importance attached to continuity between school and family times.